The Psychological Analysis of The Main Character in The Movie John Wick - Manuputty, Altur (Departemen Sastra Asia Barat, Fakultas Ilmu budaya, Universitas Hasanuddin, 2025)
This study explores the psychological analysis of the main character in John Wick (2014), emphasizing the emotional and motivational factors that drive his actions. By applying Bernhardt's psychological aspects and Kenney's conflict theory, the research investigates the protagonist's internal struggles alongside his external challenges. Key issues examined include grief, trauma, and the pursuit of justice, highlighting how these elements shape character development and influence the narrative's progression. Utilizing a qualitative descriptive method and thorough film analysis, the study reveals that John Wick's journey transcends mere revenge; it represents a complex psychological quest for closure, identity, and moral reconciliation. The findings emphasize the significance of emotions, ethical dilemmas, and personal values in character-driven narratives, illustrating how internal conflicts affect external actions. This research adds to broader discussions on the psychological depth of cinematic characters and underscores the universal themes of loss and resilience. Future studies could investigate similar analyses across different genres to deepen our understanding of character psychology and audience engagement.